\(K=\left(\frac{\sqrt{a}}{2}-\frac{1}{2\sqrt{a}}\right)^2.\left(\frac{\sqrt{a}-1}{\sqrt{a}+1}-\frac{\sqrt{a}+1}{\sqrt{a}-1}\right)\) với \(a>0\)và \(a\ne1\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x+2\sqrt{3}=4\Leftrightarrow x=4-2\sqrt{3}\)
Thay x vào biểu thức B:\(=\left(4-2\sqrt{3}\right)^6-7\left(4-2\sqrt{3}\right)^5-3\left(4-2\sqrt{3}\right)^4-4\left(4-2\sqrt{3}\right)^3+9\left(4-2\sqrt{3}\right)^2-40\left(4-2\sqrt{3}\right)+2035\)
\(=2015\)
A=(a4-2a3+a2) +2(a2-2a+1) +3
=(a2-a)2 + 2(a-1)2 + 3 \(\ge\)3
Dấu bằng xay ra khi a=1
A=a4 -2a3 +3a2 -4a +5
=a4 -2a3 +a2 +2a2-4a+2+3
=(a4 -2a3 +a2) +2(a2 -2a +1)+3
=(a2-a)2 +2(a-1)2 +3
\(\hept{\begin{cases}\left(a^2-a\right)^2\ge3\\2\left(a-1\right)^2\ge3\end{cases}\Rightarrow A_{Min}=3}\)
\(=\left(\frac{a-1}{2\sqrt{a}}\right)^2.\left(\frac{\left(\sqrt{a}-1\right)^2-\left(\sqrt{a}+1\right)^2}{\left(a-1\right)}\right)\)
\(=\frac{\left(a-1\right)^2}{4a}.\frac{a-2\sqrt{a}+1-a-2\sqrt{a}-1}{a-1}\)
\(=\frac{a-1}{4a}.-4\sqrt{a}\)
\(=\frac{a-1}{\sqrt{a}}\)